EXPERIMENTAL STUDY OF HEAT AGENT VELOCITY AND LOCAL RESISTANCE COEFFICIENTS IN HEAT EXCHANGE - Madaminova Gulmirakhon Ikromaliyevna (American Journals Publishing, 2023)
In the article, the speed of heat agent and local resistance coefficients in the process of heat exchange in a drum dryer for drying mineral fertilizers were experimentally studied, and an experimental research program was carried out in order to determine the parameters determining the high intensity of heat exchange.
Keywords: Heat exchange, drum dryer, drying, U-shaped nozzle, heater, drying rate, ch injection speed, q is the coefficient of abundance.